Practical training report: Unit Pengurusan Sumber Manusia Jabatan Ketua Menteri Sarawak / Abdul Rahim Abdul Kadir - Abdul Kadir, Abdul Rahim (University Technology MARA Sarawak, 2014)
The story ofthe Sarawak Civil Service initially started during the era ofJames Brooke. It was first known as Sarawak Administrative Service (SAS) established by James Brooke when he was given the territory of Sarawak in 1841. In 1842, James Brooke proclaimed Rajah of Sarawak. Introduced by Rajah James Brooke, Sarawak administration depicts from European style of administration originated from India and Africa. The formation of Sarawak Administrative service and the selection of officers were mainly from Brooke relatives and colleagues. Two departments that were established in 1864 are Post Office and Treasury department which were staffed by 4 European and 2 Malays.